International Evidence on Aggregate Short-Run and Long-Run Interfuel Substitution - Serletis, Apostolos; Timilsina, Govinda; Vasetsky, Olexandr (2012)
In this paper, we build on recent work by Serletis et al. (2010, in press) and report short- and long-run estimates of aggregate interfuel substitution for a number of OECD and non-OECD countries. In doing so, we use recent pooled intercountry data (since 1980), and state-of-the-art advances in microeconometrics, including duality theory and flexible functional forms. Also, motivated by the widespread practice in the empirical energy demand literature of ignoring theoretical regularity, we estimate our model subject to global curvature (but not monotonicity), using methods developed by Diewert and Wales (1987). We provide inference, and also a policy perspective, using parameter estimates that are consistent with the theoretical regularity conditions of neoclassical microeconomic theory.